Supersymmetric variational energies for the confined Coulomb system - Drigo Filho, Elso [UNESP]; Ricotta, Regina Maria [UNESP] (Elsevier B.V., 2002)
The methodology based on the association of the variational method with supersymmetric quantum mechanics is used to evaluate the energy states of the confined hydrogen atom. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: supersymmetric quantum mcchanics; confinement